Environmental management elements and corporate environmental performance of SMEs in Malaysia / Hanim Norza Baba - Baba, Hanim Norza (Institute of Research, Development and Commercialization (IRDC), 2007)
This research examined the existence of environmental management practices within private limited manufacturing companies in Malaysia, and the impact on corporate environmental performance. The study examined environmental management elements that include environmental leadership, environmental process management, top management commitment, employee involvement, reward and recognition, environmental quality management programs, and pollution prevention technologies, and their relationship to corporate environmental performance.